2017
DOI: 10.1111/jvim.14898
|View full text |Cite|
|
Sign up to set email alerts
|

Gallbladder Mucocele: Variables Associated with Outcome and the Utility of Ultrasonography to Identify Gallbladder Rupture in 219 Dogs (2007–2016)

Abstract: BackgroundGallbladder mucocele (GBM) is an increasingly recognized extrahepatic biliary disease in dogs.ObjectivesTo investigate cases of GBM and identify variables associated with survival and the sensitivity and specificity of ultrasonography to identify gallbladder rupture.AnimalsTwo hundred and nineteen client‐owned dogs with GBM.MethodsMulticenter, retrospective study of dogs with GBM, presented from January 2007 to November 2016 to 6 academic veterinary hospitals in the United States. Interrogation of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 20 publications
7
91
1
Order By: Relevance
“…Gall bladder rupture was not shown to have a negative effect on survival although this could reflect a type II error due to the low numbers of dogs with rupture in this study. A recent larger study found that dogs with rupture of the gall bladder were 2.7 times more likely to die than dogs without rupture . In this study, dogs that underwent cholecystectomy and survived the initial perioperative period had an extended survival time (MST still not reached), in agreement with previous studies …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gall bladder rupture was not shown to have a negative effect on survival although this could reflect a type II error due to the low numbers of dogs with rupture in this study. A recent larger study found that dogs with rupture of the gall bladder were 2.7 times more likely to die than dogs without rupture . In this study, dogs that underwent cholecystectomy and survived the initial perioperative period had an extended survival time (MST still not reached), in agreement with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…The 10% (6/63) incidence of positive culture of gallbladder contents (bile or gallbladder wall) is within the 3%‐70% range of previous reports and might have been underestimated by pre‐operative antibiotic therapy (not investigated in this study). Pathogens identified in the gallbladder contents and liver in this study have been reported …”
Section: Discussionsupporting
confidence: 67%
“…Population characteristics of this cohort have been previously reported . As stated in Jaffey et al, 219 dogs fulfilled inclusion criteria of the study from January 2007 to November 2016 from Iowa State University College of Veterinary Medicine (n = 23), Oklahoma State University Center for Veterinary Health Sciences (19), The Ohio State University Veterinary Medical Center (51), University of Florida College of Veterinary Medicine (40), University of Georgia College of Veterinary Medicine (50), and University of Missouri Veterinary Health Center (36).…”
Section: Resultsmentioning
confidence: 99%
“…Data retrieved from medical records included: signalment, gallbladder histological findings, antimicrobial administration within 48 hours preceding (preoperative) surgery or intraoperatively, the presence of bacteriological growth, outcome (ie, survival to discharge), and cause of death. Some data from this cohort of dogs were previously reported in a separate study with different objectives and hypotheses . Cholecystitis was defined by the identification of cholecystitis within the histopathology report or mention of various forms of inflammation (eg, suppurative, lymphocytic, lymphoplasmacytic, histiocytic, granulomatous) or inflammatory immune cells (eg, neutrophils, macrophages, lymphocytes, plasma cells) within the gallbladder wall.…”
Section: Methodsmentioning
confidence: 99%
“…Gallbladder mucoceles are life-threatening, commonly requiring immediate cholecystectomy, whereas sludge may require only medical intervention or monitoring. 5,[9][10][11][12][13][14] Ultrasound has been the conventional tool for diagnosis of gallbladder mucoceles and differentiation from biliary sludge; however, with the growing utilization of CT, the appearance of a potentially fatal gallbladder disease is not known.…”
Section: Introductionmentioning
confidence: 99%